An FMECA-based approach to process analysis. (11th May 2006) - Bertolini, Massimo; Braglia, Marcello; Carmignani, Gionata
This paper presents a new methodological approach named 'Dysfunction Mode and Effects Critical Analysis' (DMECA) to determine and analyse possible dysfunctions in complex management processes. The proposed approach is conceptually derived from the Failure Mode Effect and Criticality Analysis (FMECA) technique. The method represents an analytical tool to work according to the new ISO 9000:2000 standard and the Total Quality Management (TQM) principle concerning the 'process approach'. DMECA enables users to: build a systematic structure (map) of a management process; evaluate potential dysfunctions of the elementary activities comprising the process; evaluate a Risk Priority Number (RPN) for each cause of dysfunction; support the definition and evaluation of the possible improvement actions in a structured way. In order to illustrate the performance and characteristics of the technique, an industrial application concerning an analysis of the order process in an Engineering-to-Order (ETO) company is reported.